PENEMPATAN PASUKAN AMERIKA SERIKAT DI NIGER SEBAGAI BAGIAN DARI KEBIJAKAN GLOBAL WAR ON TERROR TAHUN 2013 - 2017 - Nanda Wijaya, Dewa Made; Dharmiasih, D.A. Wiwik; Widya Nugraha, A.A. Bagus Surya (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2019)
United States as the victim of 9/11 tragedy launch the Global War on Terror to combat global terrorism and to secure its national security. Sahel as a region passed by the Sahara Dessert is becoming a place to hide, recruit, financing and training camp for global terrorist network. The rise of terrorist network in the Sahel cannot be separated from Sahel States condition which been categorized as least developed countries. To counter the rise of terrorist threat in the Sahel Region. United States deploy its military forces in Niger. This research analyzes and describe the objective of United States military deployment in Niger, especially from 2013 until 2017. This research used security and counterterrorism framework to explain the objective of United States military deployment in Niger. Methodology that used in this research is qualitative-descriptive. Data in this research were gathers from multiple sources such as book, journal, and government reports that related with this research. Keywords: United States of America, Niger, Security Cooperation, Counterterrorism.